2020
DOI: 10.21037/jtd.2020.01.25
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase family gene polymorphisms and lung cancer susceptibility: an updated meta-analysis

Abstract: Background: Many studies have investigated the association between matrix metalloproteinase polymorphisms and lung cancer susceptibility. However, the results are still controversial. To clarify these associations, we conducted a meta-analysis. Methods: A systematic search of studies was conducted in PubMed, Embase, and China National Knowledge Infrastructure. Overall and subgroup analysis stratified by ethnicity was conducted. OR with 95% CI was used to assess the strength of the association. Furthermore, fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…In contrast it was a protective factor for nasopharyngeal and laryngeal cancers (ENT), esophageal cancer, gastric cancer, head and neck cancer and lung cancer. This result is in general agreement with previously published studies [12][13][14] [15][16]. In a subgroup analysis for different ethnic groups, we found that the rs243865 variant was associated with reduced cancer risk in East Asian populations and was instead a risk factor in South Asian populations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast it was a protective factor for nasopharyngeal and laryngeal cancers (ENT), esophageal cancer, gastric cancer, head and neck cancer and lung cancer. This result is in general agreement with previously published studies [12][13][14] [15][16]. In a subgroup analysis for different ethnic groups, we found that the rs243865 variant was associated with reduced cancer risk in East Asian populations and was instead a risk factor in South Asian populations.…”
Section: Discussionsupporting
confidence: 93%
“…The results of a meta-analysis including 29 eligible studies showed that the rs243865 C/T genotype was associated with reduced cancer risk [9]. Another meta-analysis based on 24 studies published several years later prompted that the rs243865 C/T and rs2285053 C/T variants may reduce the risk of lung cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…( 34 , 127 , 139 , 145 )( Table 4 ). In addition, subgroup analyses by ethnicity identified significant association with LC risk in Asians, while ethnicity among Caucasian had no relationship with LC susceptibility ( 34 ) ( Table 4 ), the results are consistent with the conclusion in another meta-analysis conducting on 24 studies with 10,099 LC cases and 9,395 controls ( 136 ). Possibly, genotypes varied between ethnic populations, therefore, there are differences of susceptibility to LC among various between ethnic populations.…”
Section: Effects Of Mmp Polymorphisms On Risk Of Lcsupporting
confidence: 87%
“…The role of specific MMPs and ADAMs in breast [6,72,73], lung [74][75][76][77], prostate [78][79][80], and colorecta [81] cancer progression, invasion, and metastasis has been studied extensively [18,49,82]. MPs carry a multifaceted role in cancer and they can act as a pro-tumorigenic, anti-tumorigenic, or null factor [6], making it difficult to draw a general conclusion on the role of all MPs without considering all the parameters involved in the model of study such as the individual genomic profile, proteomic profile, and experimental conditions.…”
Section: Mps In Cancermentioning
confidence: 99%